The Thin Moral Concept of Evil - Wilby, Michael (Studia z Historii Filozofii, 2022)
Evil-scepticism comes in two varieties: one variety is descriptive, where it is claimed that the concept of evil does not successfully denote anything in the world; the other variety is normative, where it is claimed that the concept of evil is not a helpful or useful concept to be employing in either our social or interpersonal lives. This paper argues that evil-scepticism can be responded to by understanding the concept of evil as a thin moral concept. Understood in this thin way, the descriptive challenge fades, because the concept of evil does not even purport to denote anything in the world (it is purely evaluative), and so does the normative argument, since the thinness of the concept means that, first, it is ineliminable anyway, and, second, its malleability allows for it to be used for progressive and constructive means.